(untitled) (Bioscience Journal, 2018)
The knowledge of the processes that affect soil herbicide behavior allows to developing practices that improve efficiency in chemical weed control and reduce the negative impacts of cropping-systems. In this research, we used HPLC to determine sorption and desorption of clomazone in Brazilian soil samples (Red-Yellow Latosol with liming and without liming, Red latosol with and without liming, and Organosol). To study clomazone sorption, we used the batch equilibrium method. Clomazone concentrations in soil samples were determined by HPLC. Desorption was quantitated using the samples contained in tubes after sorption testing, repeating the steps followed to quantify sorption. The Freundlich isotherm adequately describe clomazone sorption in all soils. Variation in pH in Red-Yellow Latosol and Red Latosol did not change clomazone sorption. The values of the Freundlich constant (Kf) indicate that clomazone sorption is higher in Organosol, followed by Red latosol (with liming) = Red latosol (without liming) > Red-Yellow Latosol (with liming) = Red-Yellow Latosol (without liming). We conclude that among the attributes evaluated, soil organic matter has the highest impact on clomazone sorption. There was a direct relationship between Kf values and organic matter content of the substrates. Desorption of clomazone was very low in the evaluated soils, with the exception of Organosol, where quantification of the herbicide was possible.